A method for preparing a perovskite solar cell device with a hole transport layer doped to optimize the perovskite solar cell device

By doping EDTA-2Na in the PEDOT:PSS layer, the acidity and hygroscopicity of the hole transport layer in the tin-based perovskite solar cell device are solved, and the photoelectric conversion efficiency and stability of the device are improved.

CN114899330BActive Publication Date: 2025-05-02NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210543716.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-19
Publication Date
2025-05-02
Estimated Expiration
2042-05-19

AI Technical Summary

Technical Problem

Among the existing tin-based perovskite solar cell devices, the hygroscopicity and acidity of the PEDOT:PSS hole transport layer affect the device performance, resulting in poor efficiency and stability.

Method used

The performance of the hole transport layer is optimized by doping disodium ethylenediaminetetraacetate (EDTA-2Na) into the PEDOT:PSS layer.

Benefits of technology

It effectively improves the photoelectric conversion efficiency and device stability of tin-based perovskite solar cells, and improves the open circuit voltage and fill factor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114899330B_ABST
    Figure CN114899330B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of photovoltaics, and particularly relates to a preparation method for optimizing a perovskite solar cell device with a doped and modified hole transport layer. The PEDOT:PSS+EDTA-2Na composite film plays multiple roles at the interface between the perovskite and the hole transport layer (HTL). This doping method is suitable for improving the energy level matching between the hole transport layer and the perovskite absorption layer, and increasing the open-circuit voltage V oc ; compared with the original PEDOT:PSS, the PEDOT:PSS layer modified by EDTA-2Na has a greater roughness, forming a mosaic structure between the hole transport layer and the active layer, which is conducive to the penetration of the active layer and the separation of excitons at the interface. Moreover, the aggregation of the PEDOT layer will increase its conductivity, thereby optimizing the device performance; it is conducive to the seed-mediated growth of perovskite, making the perovskite film dense and uniform, with excellent crystallinity and low defect density, ultimately promoting the improvement of the efficiency and stability of the tin-based perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photovoltaics, and in particular relates to a method for preparing a perovskite solar cell device by optimizing a doped hole transport layer. Background Art

[0002] As the third generation of solar cells, perovskite solar cells have a good development status. Today, the photoelectric conversion efficiency of perovskite solar cells has reached 25.7%. The environmental problems caused by lead-based perovskite solar cells limit their further application. Compared with lead-based perovskites, tin-based perovskites are the most promising alternatives that exhibit similar or superior electronic and optical properties such as higher carrier mobility and long-lived hot carriers. However, the crystallization of tin-based perovskite absorber films is complex, the growth is uncontrollable, and the Sn in the film is 2+ Easily oxidized to Sn in the air 4+ , so the overall performance of tin-based perovskite solar cells is poor.

[0003] For inverted tin-based perovskite solar cell devices, the hole transport layer (HTL) is usually essential for effectively blocking electrons and transporting holes. In addition, it also affects the quality of the upper perovskite layer and directly affects the efficiency and stability of the device.

[0004] PEDT:PSS is an aqueous dispersion of poly(3,4-ethylenedioxythiophene) poly(styrene sulfonate). A series of polymers polymerized from PEDOT monomers, PEDOT:PSS can be dispersed in water and some organic solvents, and high-quality films can be made using traditional solution-based coating methods. PEDOT:PSS thin film materials are low-cost, have excellent thermal stability and high mechanical flexibility, are uniform and highly transparent in the visible light range, and the conductivity can be increased by 10 under certain synthesis conditions, using different additives or post-treatment methods. -2 to 10 3 S / cm. Therefore, PEDOT:PSS is the most popular hole transport layer material (HTL) in inverted perovskite solar cells.

[0005] PEDOT:PSS is a polyelectrolyte with positively charged conjugated PEDOT and negatively charged non-conjugated PSS. They are bound together by strong Coulomb attraction. PEDOT is conductive and hydrophobic, while PSS is non-conductive, hydrophilic, and acidic. However, the hygroscopicity and acidity of PEDOT:PSS can affect the device performance of the battery. Hygroscopicity causes PEDOT:PSS to absorb moisture from the environment, causing the perovskite absorber layer to decompose, and the acidity can corrode the ITO electrode. Therefore, optimizing the properties of PEDOT:PSS is crucial for fabricating PSCs with long-term stability. Optimizing the pH value, hydrophilicity, work function, surface morphology, and conductivity of the PEDOT:PSS layer can improve the PCE and stability of PSCs. Generally speaking, modification methods can be divided into three types: doping, post-treatment, and using a double layer.

[0006] To solve this problem, some strong bases (such as KOH, NaOH and guanidine) have been used to neutralize the acidity of PEDOT:PSS. However, the neutralization process of strong bases will have an adverse effect on the charge transport properties of PEDOT:PSS, resulting in reduced device efficiency, so later researchers prefer to use milder bases. The energy level mismatch between PEDOT:PSS (about -5.0 eV) and the perovskite active layer (for example, the work function of FASnI3 is -5.9 eV) leads to reduced device efficiency and stability. This is because the energy barrier at the PEDOT:PSS / perovskite interface not only inhibits the transfer of holes from perovskite to PEDOT:PSS, but also enhances the interfacial recombination, resulting in V oc Low, poor stability. Therefore, regulating the electronic properties of PEDOT:PSS is crucial to improving device stability. In order to achieve better energy level matching, researchers doped NaCl into PEDOT:PSS to adjust its work function and obtained an excellent V of 1.52 V in CH3NH3PbI3-based PSCs. oc The PSCs with modified PEDOT:PSS hole transport layer can maintain more than 85% of their original PCE after being stored in N2 atmosphere for 60 days. The study found that doping with sodium salt can effectively adjust the energy level of the hole transport layer and obtain excellent open circuit voltage.

[0007] Disodium ethylenediaminetetraacetate, referred to as EDTA-2Na, is a chelating agent containing carboxyl and amino groups, and has a wide range of coordination properties. It has the characteristics of large molecular volume, strong coordination ability, and easy removal. In this invention, we first introduced disodium ethylenediaminetetraacetate (EDTA-2Na) as a dopant into the PEDOT:PSS layer. Since EDTA-2Na has six coordinated ions, it can effectively change the acidity of the PEDOT:PSS solution and optimize the work function and interface barrier. Therefore, the overall device performance and long-term stability of FASnI3-based PSCs can be effectively improved. Summary of the invention

[0008] The purpose of the present invention is to solve the influence of hygroscopicity and acidity of PEDOT:PSS on the performance of battery devices, and to provide an effective doping method, which not only makes the energy levels between the hole transport layer and the perovskite absorption layer more matched, but also increases the hole mobility and obtains excellent open circuit voltage (V oc ); At the same time, doping EDTA-2Na in PEDOT:PSS can effectively improve the film quality of FASnI3 film, make the grain size of perovskite film larger and more uniform, and improve the photoelectric conversion efficiency and device stability of tin-based perovskite solar cells.

[0009] In order to solve the problems of the prior art, the technical solution adopted by the present invention is as follows:

[0010] The material of the improved hole transport layer in the present invention is a PEDOT:PSS solution doped with different concentrations of EDTA-2Na, with specific concentrations of 0.8 mg / mL, 2.0 mg / mL, 2.5 mg / mL, 5.0 mg / mL, 7.5 mg / mL, 10.0 mg / mL, and 20.0 mg / mL. The proportioning method is to dilute the solution with a small doping concentration by proportioning a doping solution with a large concentration to ensure the accuracy of the doping concentration. After the solution is prepared, a magnet is added and placed on a magnetic stirring table to fully stir until the sodium salt powder is completely dissolved in the PEDOT:PSS solution for standby use.

[0011] Take the same number of injection needles according to different doping concentrations, absorb the solution and replace it with a 0.45 μm PVDF filter for filtration, then drop the PEDOT:PSS solution on the ITO substrate to completely cover it. The setting parameters of the spin coater are 5000 rpm and 40 s. After the spin coating stops, remove the substrate and place it on a clean annealing table. Anneal it at 140°C in air for 15-20 min to form a hole transport layer. Distinguish PEDOT:PSS solutions with different doping concentrations according to the number.

[0012] The technical solution provided by the present invention is a method for improving a tin-based perovskite solar cell device by doping a PEDOT:PSS hole transport layer with EDTA-2Na, wherein the solar cell comprises, from bottom to top, an ITO conductive glass layer, a hole transport layer, a perovskite absorption layer, an electron transport layer, a hole blocking layer and an electrode. EDTA-2Na is dissolved in a hole transport material PEDOT:PSS at a doping ratio of 5.0 mg / mL to prepare a PEDOT:PSS+EDTA-2Na solution.

[0013] The solar cell device includes an ITO conductive glass layer, a PEDOT:PSS hole transport layer, a lead-free perovskite absorption layer, a C60 electron transport layer, a BCP hole blocking layer and an Ag electrode stacked in sequence. The perovskite absorption layer is prepared by spin coating on the hole transport layer, the electron transport layer is prepared by evaporating C60 material on the perovskite absorption layer, the hole blocking layer is prepared by evaporating BCP on the electron transport layer, and the electrode layer is prepared by evaporating an Ag electrode on the hole blocking layer.

[0014] Compared with the existing technology, the present invention has the following advantages:

[0015] 1. We first introduced disodium ethylenediaminetetraacetate (EDTA-2Na) as a dopant into the PEDOT:PSS layer. Since EDTA-2Na has six coordinated ions, it can effectively change the acidity of the PEDOT:PSS solution and optimize the work function and interface barrier, thus effectively improving the overall device performance of FASnI3-based PSCs.

[0016] 2. When disodium ethylenediaminetetraacetate (EDTA-2Na) is used as an additive, the roughness of the PEDOT:PSS layer modified by EDTA-2Na is greater than that of the original PEDOT:PSS, so that the hole transport layer and the active layer form a mosaic structure, which is beneficial to the penetration of the active layer and the separation of excitons at the interface. The agglomeration of the PEDOT layer increases its conductivity, thereby optimizing the device performance.

[0017] 3.EDTA-2Na is an important complexing agent used for complexing metal ions and separating metals. It has a wide source, low cost, and is safe to use. It will not cause secondary pollution during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a structural diagram of a perovskite solar cell device prepared in Example 1;

[0019] Figure 2 The structural formula of EDTA-2Na, the hole transport layer doping material in Example 1;

[0020] Figure 3 It is the energy level diagram of each functional layer of the perovskite solar cell;

[0021] Figure 4 is a JV curve diagram of the perovskite solar cell device prepared in Comparative Example 1 and Example 1;

[0022] Figure 5 is the XRD diagram of the perovskite light absorbing layer FASnI3 film prepared in Comparative Example 1 and Example 1;

[0023] Figure 6is an AFM image of the hole transport layer film prepared in Comparative Example 1;

[0024] Figure 7 is an AFM image of the hole transport layer film prepared in Example 1;

[0025] Figure 8 is a SEM image of the FASnI3 film prepared in Comparative Example 1;

[0026] Fig. 9 This is the SEM image of the FASnI3 thin film prepared in Example 1. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0028] The PEDOT:PSS aqueous solution used in the present invention is a commercially available reagent, CAS No. 155090-83-8, with a concentration of 1.3%-1.7% aqueous solution, a dark blue liquid, and is stored in a nitrogen environment at 2-8 degrees Celsius and away from light. The present invention uses it directly.

[0029] Comparative Example 1

[0030] 1. Preparation of precursor solution: Dissolve tin iodide SnI, formamide FAI, and tin fluoride SnF in a mixed solvent of N,N-dimethylformamide DMF and dimethyl sulfoxide DMSO solution at a molar ratio of 1:1:0.1 (the volume ratio of DMF and DMSO is 4:1). Stir the mixed solution at room temperature for 24 hours to obtain a perovskite precursor solution with a concentration of 1 mol / L for standby use;

[0031] 2. Substrate pretreatment: Wash the ITO conductive glass sheet twice with washing solution, deionized water, acetone and ethanol respectively, put the ITO substrate into a constant temperature oven at 80℃ for more than half an hour for drying, and then perform plasma treatment for 2 minutes after drying;

[0032] 3. Preparation of hole transport layer: Spin PEDOT:PSS on the treated ITO conductive glass at a speed of 5000 rpm using a spin coater for 40 s, and anneal at 130°C in air for 20 min to form a hole transport layer;

[0033] 4. Preparation of perovskite light-absorbing layer: put the annealed wafer into a glove box, spin-coat the perovskite precursor solution onto the PED0T:PSS+EDTA-2Na layer at a speed of 5000 rpm for 30 s, and quickly drop-coat chlorobenzene after 13 s of spin coating. Anneal at 100°C for 10 min to form a perovskite light-absorbing layer.

[0034] 5. Preparation of electron transport layer: Fullerene C60 was evaporated on the perovskite light absorption layer using vacuum evaporation equipment. The thickness of C60 was 20 nm, the evaporation rate was 0.1 Å / s, and the pressure environment of the evaporation was less than 4X10 -4 Pa;

[0035] 6. Preparation of hole blocking layer: The organic small molecule material 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was evaporated using vacuum evaporation equipment to form a hole blocking layer. The thickness of the hole blocking layer was 8 nm, the evaporation rate was 0.4 Å / s, and the evaporation pressure environment was less than 4X10 -4 Pa;

[0036] 7. Preparation of metal cathode: Metal Ag is evaporated on the hole blocking layer to form a metal cathode layer. The thickness of the metal cathode layer is 100 nm, the evaporation rate is 0.8 A / s, and the evaporation pressure environment is less than 4X10 -4 Pa;

[0037] At room temperature, measure the JV curve of the device, such as Figure 3 As shown in the figure, it can be seen that the open circuit voltage of the device is 0.34476V and the short circuit current is 16.28 mA / cm 2 , the filling factor is 0.6819 and the efficiency is 3.83%.

[0038] Example 1

[0039] 1. Preparation of precursor solution: Dissolve tin iodide SnI, formamide FAI, and tin fluoride SnF in a mixed solvent of N,N-dimethylformamide DMF and dimethyl sulfoxide DMSO solution at a molar ratio of 1:1:0.1 (the volume ratio of DMF and DMSO is 4:1). Stir the mixed solution at room temperature for 24 hours to obtain a perovskite precursor solution with a concentration of 1 mol / L for standby use;

[0040] 2. Substrate pretreatment: Wash the ITO conductive glass sheet twice with washing solution, deionized water, acetone and ethanol respectively, put the ITO substrate into a constant temperature oven at 80℃ for more than half an hour for drying, and then perform plasma treatment for 2 minutes after drying;

[0041] 3. Preparation of hole transport layer: Dissolve EDTA-2Na in hole transport material PEDOT:PSS at a doping ratio of 5.0 mg / mL to form PEDOT:PSS+EDTA-2Na solution, add a magnet and place on a magnetic stirring table to stir until completely dissolved, and set aside. Spin-coat the doped and modified hole transport material solution onto the conductive glass at a spin-coating speed of 5000 rpm, a spin-coating time of 40 s, an annealing temperature of 140 °C, and an annealing time of 15-20 min. After annealing, an improved hole transport layer film is formed;

[0042] 4. Preparation of perovskite light-absorbing layer: put the annealed wafer into a glove box, spin-coat the perovskite precursor solution onto the PED0T:PSS+EDTA-2Na layer at a speed of 5000 rpm for 30 s, and quickly drop-coat chlorobenzene after 13 s of spin coating. Anneal at 100°C for 10 min to form a perovskite light-absorbing layer.

[0043] 5. Preparation of electron transport layer: Fullerene C60 was evaporated on the perovskite light absorption layer using vacuum evaporation equipment. The thickness of C60 was 20 nm, the evaporation rate was 0.1 Å / s, and the pressure environment of the evaporation was less than 4X10 -4 Pa;

[0044] 6. Preparation of hole blocking layer: The organic small molecule material 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) was evaporated using vacuum evaporation equipment to form a hole blocking layer. The thickness of the hole blocking layer was 8 nm, the evaporation rate was 0.4 Å / s, and the evaporation pressure environment was less than 4X10 -4 Pa;

[0045] 7. Preparation of metal cathode: Metal Ag is evaporated on the hole blocking layer to form a metal cathode layer. The thickness of the metal cathode layer is 100 nm, the evaporation rate is 0.8 Å / s, and the evaporation pressure environment is less than 4X10 -4 Pa.

[0046] At room temperature, measure the JV curve of the device, such as Figure 4 As shown in the figure, it can be seen that the open circuit voltage of the device is 0.4202 V and the short circuit current is 17.42 mA / cm 2 , the filling factor is 0.6905 and the efficiency is 5.05%.

[0047] In order to explore the optimal doping concentration of the present invention, the PEDOT:PSS+EDTA-2Na solution with the content of EDTA-2Na of 0.8 mg / mL-20.0 mg / mL was specifically formulated. The experiment found that the device performance changed with the change of doping concentration, among which the most significant change was the change of open circuit voltage (Voc). The Voc of comparative example 1 was 0.344 V. As EDTA-2Na was incorporated into the PEDOT:PSS layer, Voc gradually increased, reaching a maximum value of 0.420 V when the content of EDTA-2Na was 5.0 mg / mL. At the same time, the optimal current density Jsc of this embodiment was 17.42 mA / cm2, and the improved fill factor (FF) was 69.05%. Finally, the maximum photoelectric conversion efficiency (PCE) of 5.06% was achieved, which was about 32% higher than that of the comparative example of 3.83%. However, the further increase in the content of EDTA-2Na caused the open circuit voltage (Voc), current density (Jsc) and fill factor (FF) of the device to gradually decrease.

[0048] Concentration <![CDATA[V oc (V)]]> <![CDATA[J sc (mA / cm 2 )]]> FF PCE (%) Comparative Example 1 0.344 16.28 68.20 3.83 0.8 mg / mL 0.388 15.98 63.37 3.91 2.0 mg / mL 0.390 16.46 63.73 4.09 2.5 mg / mL 0.405 16.76 62.41 4.24 Example 1 (5.0 mg / mL) 0.420 17.42 69.05 5.06 7.5 mg / mL 0.374 16.48 63.94 3.94 10.0 mg / mL 0.344 16.36 57.46 3.24 20.0 mg / mL 0.344 14.94 54.83 2.83

[0049] In order to understand the V of the device after adding 5.0 mg / mL EDTA-2Na to the PEDOT:PSS layer, oc The reason for the significant improvement was investigated using UPS characterization to investigate the surface state of the PEDOT:PSS layer, e.g. Figure 3 As shown in the figure, after doping, the work function of PEDOT:PSS changes from -5.10 eV to -5.85 eV, which better matches the valence band of the perovskite layer of -5.90 eV.

[0050] The crystallinity and changes of the perovskite film deposited on PEDOT:PSS were studied by XRD test, such as Figure 5 As shown, the diffraction peak of the perovskite film on PEDOT:PSS after EDTA-2Na doping is significantly higher than that of the undoped one, indicating that the crystallinity of the perovskite film is better after doping.

[0051] In order to explore the surface morphology of the hole transport layer before and after doping, AFM tests were performed on the hole transport layer. Figure 6 and Figure 7 As shown, compared with the original PEDOT:PSS, the roughness of the PEDOT:PSS layer modified by EDTA-2Na is greater, so that the hole transport layer and the active layer form a mosaic structure, which is beneficial to the penetration of the active layer and the separation of excitons at the interface. The agglomeration of the PEDOT layer increases its conductivity, thereby optimizing the device performance.

[0052] In order to explore the changes in the surface morphology of the perovskite film, the changes in the surface morphology of Comparative Example 1 and Example 1 were studied by scanning electron microscopy (SEM). Figure 8 and Fig. 9 As shown, it was found that the surface morphology was smoother, the grain size became larger, and the grain boundaries were reduced, so doping EDTA-2Na in PEDOT:PSS can effectively improve the film quality of FASnI3 film.

[0053] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a doped hole transport layer optimized perovskite solar cell device, characterized in that: The solar cell device comprises an ITO conductive glass layer, a hole transport layer, a perovskite absorption layer, an electron transport layer, a hole blocking layer and an electrode layer stacked in sequence; the preparation method steps used are as follows: (1) Pretreatment of ITO conductive glass layer, (2) Spin coating on ITO; the material used is a PEDOT: PSS aqueous solution with a concentration of 1.3%-1.7%, doped with EDTA-2Na to form a PEDOT:PSS+EDTA-2Na solution, and the solution is spin coated on the pretreated ITO substrate using a spin coater; after spin coating, the substrate is removed and placed on an annealing table, and annealed in air to form a hole transport layer; (3) Preparing a perovskite absorption layer on the hole transport layer, first spin-coating a perovskite precursor solution onto the hole transport layer, adding a chlorobenzene solution dropwise during spin coating, and then performing an annealing treatment to obtain the perovskite absorption layer; (4) Vapor depositing fullerene C60 on the perovskite absorption layer to obtain an electron transport layer; (5) evaporating 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline on the electron transport layer to obtain a hole blocking layer; (6) Ag is deposited on the hole blocking layer to obtain an electrode layer.

2. The method for preparing a doped hole transport layer optimized perovskite solar cell device according to claim 1, characterized in that: The concentration of EDTA-2Na in the PEDOT:PSS aqueous solution is 0.8 mg / mL to 20.0 mg / mL.

3. The method for preparing a doped hole transport layer optimized perovskite solar cell device according to claim 1, characterized in that: The concentration of EDTA-2Na in the PEDOT:PSS aqueous solution is 5.0 mg / mL.

4. The method for preparing a doped hole transport layer optimized perovskite solar cell device according to claim 1, characterized in that: The mixing method is to first prepare the PEDOT:PSS solution, then add EDTA-2Na and stir thoroughly until the sodium salt powder is completely dissolved.

5. The method for preparing a doped hole transport layer optimized perovskite solar cell device according to claim 1, characterized in that: The solution in step (2) is filtered using a 0.45 μm polyvinylidene fluoride filter and then dripped into a spin coater.

6. The method for preparing a doped hole transport layer optimized perovskite solar cell device according to claim 1, characterized in that: In the spin coating of step (2), the setting parameters of the spin coater are a rotation speed of 5000 rpm and a spin coating time of 40 s.

7. The method for preparing a doped hole transport layer optimized perovskite solar cell device according to claim 1, characterized in that: The annealing temperature is 140° C. and the annealing time is 15-20 min.

8. The method for preparing a doped hole transport layer optimized perovskite solar cell device according to claim 1, characterized in that: The spin coating time of step (3) is 30 s, and 150 uL of chlorobenzene solution is added dropwise during the spin coating for 13 s.